Nonlinear dynamics of three-dimensional vortex-induced vibration prediction model for a flexible fluid-conveying pipe. (April 2018) - Yang, Wenwu; Ai, Zhijiu; Zhang, Xiaodong; Chang, Xueping; Gou, Ruyi
Highlights: A three-dimensional model is developed to predict the nonlinear VIV dynamics of a flexible fluid-conveying pipe. The geometric and hydrodynamic nonlinearities, internal flow, cross flow, and tension force effects are considered. Recognize the jumping phenomenon of a flexible riser with different internal and cross-flow velocities. The discontinuous jumping phenomenon of in-line response modal is discovered. The opposite variation between axial and in-line or cross-flow displacement amplitude and maximum stress within the modal transition region is revealed. Abstract: In this article, a three-dimensional nonlinear dynamic model, which takes into account both the geometric and hydrodynamic nonlinearities, is presented to characterize the behavior of a flexible fluid-conveying pipe under vortex-induced vibration by extended Hamilton's principle. It should be noted that the pipe conveying fluids is placed in a uniform cross flow. Two distributed and coupled van der Pol wake oscillators are utilized to model the fluctuating lift and drag coefficients, respectively. The finite element method is adopted to directly solve the highly coupled nonlinear fluid-structure interaction equations. Model validations are firstly performed through comparisons with published experimental data and numerical simulation results. The results show that the natural frequency will rapidly decrease with the increase of internal flow velocity. Parametric studies highlight that the maximum displacements and stresses of the riser can be increased or decreased depending on the internal flow velocity, and the critical internal flow velocities result in the increase of mode order for different cross-flow velocities. The opposite variation between axial and in-line or cross-flow displacement amplitude and maximum stress within the modal transition region is revealed. Moreover, the discontinuous jumping phenomenon of in-line response modal is discovered. Graphical abstract: Image, graphical abstract